Olive Oil and Vegetable Extract in Modified Hospital Enteral Formula Improves Glycemic Variability in Critically-Ill Diabetic Ketoacidosis Obese Patient: A Case Report - Anindhita, Bintari; Singal, Anna Maurina; Wardhani, Wahyu Ika; Manikam, Nurul Ratna Mutu; Aditianingsih, Dita (Majalah Anestesia & Critical Care, 2024)
Background: Severe hyperglycemia in diabetic ketoacidosis may elevate pro inflammatory cytokines, oxidative stress, and metabolic disruptions, impacting the nutritional status of critically ill patients. Diabetes-specific formula (DSF) administration is linked to favorable glycemic control, but research on the role of modified hospital enteral formulas in diabetic critical illness is lacking. Case Description: An obese 29-year-old male at risk of malnutrition, presented to the emergency room with decreased level of consciousness due to metabolic encephalopathy, diabetic ketoacidosis due to suspected type 1 diabetes mellitus, hypertension, and acute kidney injury. Medical nutritional therapy was provided via enteral route according to recent ESPEN, ASPEN and ADA recommendation. The administered enteral formula was a modified hospital-based enteral formula, consisting of a special kidney hospital-based enteral formula mixed with olive oil as source of monounsaturated fatty acid (MUFA) and vegetables as source of fibers. During the first week of hospitalization, the patient’s coefficient of variation (%CoV) of glycemic variability ranged between 17–61%, in addition, at the beginning of the second week of treatment there was also an increase in glycemic variability to 53%. This could be influenced by several factors. However, improvement in glycemic variability was observed in the following days. This improvement was in line with the gradual increase in MUFA and fiber intake, which reached its highest intake during the second week of hospitalization. Conclusion: Hospital-based enteral formula modified with olive oil and vegetable extract can be made to resemble the nutrients composition of diabetes specific formula and has a favorable effect on glycemic variability.